Analisis Pengelolaan Surat Yang Masuk Pada Bidang Penaatan Dan Peningkatan Kapasitas Lingkungan Hidup Terhadap Surat Perintah Tugas Dan Surat Perintah Perjalanan Dinas Di Sumatera Utara Dengan Menggunakan Metode Regresi - Annisa, Nur Alvi; Nurmadani; Fadillah, Yanna Rezki; Lubis, Riri Syafitri (Unity Academy, 2022)
Practical Work (KP) is an academic activity that is oriented towards forms of student learning to develop and improve a quality workforce. With practical work (KP) it is hoped that students will be able to add to their knowledge and experience in preparing themselves to enter the real world of work. problems that occur in the field of compliance and environmental capacity building in North Sumatra province, namely the preparation of data for incoming and outgoing letters which are still manual using a ledger which is then inputted with a computer which still uses Excel as a place to store personal data with different data, officers do 2 work times. therefore the practitioner tries to use the linear regression method to determine the effect between the two to make it more efficient.